Gambaran Karakteristik Kepatuhan Penderita Hipertensi Dengan Di Puskesmas Ngaliyan Kota Semarang - Farizi, Gilang Rizki Al; Aprilia, Eka Rosita; Gloria, Fransisca; Dewi, Rissa Maharani; Suwarni, Sri (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Abstract: Hypertension is a disease that is often found in Indonesia. A person is said to have hypertension if systolic blood pressure >140 mmHg and diastolic pressure >90mmHg. Adherence to the use of drugs plays an important role in the long-term treatment of hypertension in order to reduce the risk of complications. This study aims to determine the characteristics of compliance of hypertension patients at the Ngaliyan Health Center, Semarang City. This study used a quantitative design with observational research and cross sectional data collection using patient health medical record data for the period January - April 2023. The instruments used were MMAS-8 and Health Beliefe Model with 240 respondents who met the inclusion criteria. The results of the description of the characteristics of compliance in patients with hypertension) can be concluded that most have a moderate level of compliance as many as 130 respondents (54.2%) while respondents who have a low level of compliance are 77 respondents (32.1%) and those with high compliance are 33 respondents (13.8%).